Closure - Hitapriya Suprayitno (Departemen Teknik Sipil, Institut Teknologi Sepuluh Nopember, 2025)
Journal of Infrastructure & Facility Asset Management Volume 7, Special Issue 2, January 2025 (e) ISSN 2656-8896 (P) ISSN 2656-890X Volume 7, Special Issue 1, January 2025 Parametric Study of Embankment Stability And Geotextile Reinforcement On Soft SoilMirza Syah Alam, Herman Wahyudi, Yudhi Lastiasih, Yusrizal Kurniawan Analysis Of Slope Stability Based On The Effect Of RainFall On The Lombok International Airport (Bil) – Mandalika Road STA 10+375 to STA 10+550Made Sudiadnya, Mohamad Khoiri, Dwa Desa Warnana, Herlambang Zulfikar Analysis of The Effect of Seismic Load on The Design Safety Factor of Foam Mortar with Bored Pile Landslide Location of Batas Pidie/Aceh Besar – Bts. Kota Sigli STA 0+560Ichvan Danny Kurniawan, Trihanyndio Rendy Satrya, Ria Asih Aryani Soemitro,Fikri Afzal A Study of Pile Displacement in Soft Soil: The Case of Semarang - Demak Toll Road Construction Package 1BNovera Sagita, Herman Wahyudi, Yudhi Lastiasih &Yusrizal Kurniawan Design Of Toll Road Embankment With Secondary Compression Mitigation After PVD Installation And Solutions For The Probolinggo – Banyuwangi Toll Road Construction Project PackKAGE 2 STA 16+300 – STA 16+700Septya Kukuh Aryandi, Indrasurya B. Mochtar, Noor Endah, Abdjad Agung Artanto Volume 7, Issue 1, January 2025 Parametric Study of Embankment Stability And Geotextile Reinforcement On Soft SoilMirza Syah Alam, Herman Wahyudi, Yudhi Lastiasih, Yusrizal Kurniawan Analysis Of Slope Stability Based On The Effect Of RainFall On The Lombok International Airport (Bil) – Mandalika Road STA 10+375 to STA 10+550Made Sudiadnya, Mohamad Khoiri, Dwa Desa Warnana, Herlambang Zulfikar Analysis of The Effect of Seismic Load on The Design Safety Factor of Foam Mortar with Bored Pile Landslide Location of Batas Pidie/Aceh Besar – Bts. Kota Sigli STA 0+560Ichvan Danny Kurniawan, Trihanyndio Rendy Satrya, Ria Asih Aryani Soemitro,Fikri Afzal A Study of Pile Displacement in Soft Soil: The Case of Semarang - Demak Toll Road Construction Package 1BNovera Sagita, Herman Wahyudi, Yudhi Lastiasih &Yusrizal Kurniawan Design Of Toll Road Embankment With Secondary Compression Mitigation After PVD Installation And Solutions For The Probolinggo – Banyuwangi Toll Road Construction Project PackKAGE 2 STA 16+300 – STA 16+700Septya Kukuh Aryandi, Indrasurya B. Mochtar, Noor Endah, Abdjad Agung Artanto